MINAT SISWA SMA KELAS XII KECAMATAN SUKASARI KOTA BANDUNG TERHADAP PROGRAM STUDI S1 PGPAUD FIP UPI - Haristi, Rizka; Setiasih, Ocih; Listiana, Aan (Edukids: Jurnal Pertumbuhan, Perkembangan, dan Pendidikan Anak Usia Dini, 2017)
Abstrac : The Interest of Twelfth Grade Senior High School Students in Sukasari District Bandung City in the Undergraduate Study Program of PGPAUD FIP UPI.The research is prompted by the phenomenon of the low number of students interested in the Study Program of PGPAUD, more specifically the study program of PGPAUD FIP UPI. The low interest is contradictory to the greatly increasing demands for early childhood education teachers in the field. Therefore, the research aims to find the profile of data on the interest of twelfth grade senior high school students in Sukasari District, Bandung City, in the undergraduate study program of PGPAUD FIP UPI, as examined from school status, gender, and specialization. The method employed was cross sectional survey. The population of this research was as many as 681 twelfth grade senior high school students from all over Sukasari District for the school year of 2014-2015, and with disproportional stratified sampling, 246 students were taken as the sample. The data were collected by means of close-ended questionnaires that were then analyzed using descriptive statistic. The results show that 6.50% of the students in the District were interested in the Study Program of PGPAUD FIP UPI. In terms of school status, the percentages for private and state senior high school students interested in this study program were 7.77% and 5.60%, respectively. As regards gender, the percentages of female and male students interested in this study program were 8.87% and 4.92%, respectively. With regard to specialization in senior high school, the percentages of social sciences and natural sciences students interested in the study program were 46% and 5.17%, respectively. There are possibly three key aspects affecting this phenomenon, among others are studentsâ€™ perception of guaranteed future career for PGPAUD graduates, the influence of urban life on students, and the lack of contribution from the Study Program of PGPAUD FIP UPI to senior high school students. The research recommends that the government make appropriate policies concerning certainty of employment for early childhood education teachers and the study program of PGPAUD FIP UPI carry out promotional and extension programs.Abstrak : Minat Siswa SMA Kelas XII Kecamatan Sukasari Kota Bandung terhadap Program Studi S1 PGPAUD FIP UPI. Penelitian ini dilakukan berdasarkan fenomena rendahnya jumlah peminat Program Studi PGPAUD, khususnya Program Studi PGPAUD FIP UPI. Kondisi tersebut bertolak belakang dengan kebutuhan guru PAUD di lapangan yang semakin besar. Oleh karena itu, penelitian ini bertujuan untuk memperoleh data profil minat siswa SMA Kelas XII Kecamatan Sukasari Kota Bandung terhadap program Studi S1 PGPAUD FIP UPI yang juga ditelaah berdasarkan status sekolah, jenis kelamin, dan jurusan di SMA. Metode yang digunakan adalahÂ  survei cross sectional. Populasi penelitian ini merupakan seluruh siswa SMA Kelas XII se-Kecamatan Sukasari tahun ajaran 2014-2015 yang berjumlah 681, sedangkan sampel berjumlah 246 siswa dengan teknik disproportional stratified sampling. Alat pengumpulan data penelitian ini menggunakan angket tertutup yang kemudian dianalisis dengan statistika deskriptif. Hasil penelitian menunjukkan bahwa 6,50% siswa di kecamatan tersebut yang berminat terhadap program studi PGPAUD FIP UPI. Dilihat berdasarkan status sekolah, siswa SMA Swasta yang berminat terhadap program studi ini sebesar 7,77% dan SMA Negeri 5,60%. Dilihat berdasarkan jenis kelamin, 8,87% siswa perempuan berminat terhadap program studi ini sedangkan laki-laki sebesar 4,92%. Dilihat berdasarkan jurusan di SMA, siswa IPS memperoleh persentase minat sebesar 8,46% dan IPA 5,17%. Tiga faktor utama yang mungkin mempengaruhi kondisi tersebut diantaranya: persepsi siswa terhadap keterjaminan karier lulusan PGPAUD, pengaruh lingkungan siswa yang berada di wilayah perkotaan, dan kurangnya kontribusi Prodi PGPAUD FIP UPI di kalangan siswa SMA. Rekomendasi penelitian ini agar pemerintah membuat kebijakan yang tepat mengenai keterjaminan profesi guru PAUD dan bagi Prodi PGPAUD FIP UPI agar melaksanakan promosi dan sosialisasi.